2017
DOI: 10.1590/s0102-053620170209
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and agronomic traits of cabbage plants hybrid Fuyutoyo ® sprayed with plant growth regulators

Abstract: In this study we aimed to evaluate the effect of using the mixture of plant growth regulators auxin, gibberellin and cytokinin in the physiological behavior and productive components of cabbage plants hybrid Fuyutoyo®. The experimental design was completely randomized, with four replications, evaluating five doses of the mixture of plant growth regulators, in the form of the commercial product Stimulate® (0, 50, 100, 150 and 200 mL p.c./100 L H2O). The spray applications of plant growth regulators started when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In addition, the positive effects of Stimulate + boron were primarily due to the improvements caused by boron. Increased fruit yields using Stimulate is reported in the literature for bell peppers (Palangana et al, 2012), cabbage (Zeist et al, 2017b), and soybean (Albrecht et al, 2012). However, in the present study, Stimulate improved only the volume of marketable fruits relative to the control.…”
Section: Resultscontrasting
confidence: 52%
“…In addition, the positive effects of Stimulate + boron were primarily due to the improvements caused by boron. Increased fruit yields using Stimulate is reported in the literature for bell peppers (Palangana et al, 2012), cabbage (Zeist et al, 2017b), and soybean (Albrecht et al, 2012). However, in the present study, Stimulate improved only the volume of marketable fruits relative to the control.…”
Section: Resultscontrasting
confidence: 52%
“…It is assumed that the lower CO 2 concentration in the substomatal chamber of these plants is related to a higher use of CO 2 by ribulose-1,5bisphosphate carboxylase oxygenase (Rubisco) in the Calvin cycle for the synthesis of P-trioses. The lower Ci in plants tends to stimulate stomatal opening and transpiration, thus allowing a higher CO 2 entry into the substomatal spaces, which, consequently, promotes a higher net CO 2 assimilation (Zeist et al, 2017b), as observed for 'PI-127826' and 'PI-134417' and hybrids 'Redenção' × 'PI-127826' and 'Redenção' × 'PI-134417'.…”
Section: Methodsmentioning
confidence: 86%
“…This shows that there was a positive balance between CO 2 fixation in photosynthesis and respiration CO 2 release. Possibly due to the C i in the seedlings (3 buds), RuBisCO (ribulosebisphosphatecarboxylase-1,5-oxigenasse) was not saturated and worked efficiently, promoting a linear increase in the net assimilation rate (A), as explained by (Zeist et al 2017).…”
Section: Development Of Nursery Seedlingsmentioning
confidence: 99%